Empress Eudoxia in the Light of the 5th-Century Ecclesiastical Histories - Bralewski, Sławomir (Vox Patrum, 2020)
In the dispute between John Chrysostom, Bishop of Constantinople, and the imperial court the main role is generally attributed to Empress Eudoxia, who was blamed for causing his exile. How did the authors of Ecclesiastical histories, writing in the first half of the 5th century, perceive this empress? The first of them, Philostorgius, clearly suggested that although initially the status of Eudoxia at the imperial court was not strong because of her barbaric origin, the empress - wielding her femininity as a powerful weapon—not only managed to defend herself but also strengthened her position in the courtly environment by plunging her opponents into utter powerlessness. As for Theodoret, this historian refused to disclose the names of those guilty of John Chrysostom’s fate. He also did not attribute intentional guilt to the imperial couple, considering that their guilt was unintentional. He suggested, however, that Eudoxia’s influence at the imperial court was so great that if she wanted, she could have John return from the exile. In the case of Socrates and Sozomen, both historians, although they differed in their assessment of John Chrysostom, showed a remarkable convergence of views in the case of empress Eudoxia. They both described her with a clear restraint, pointing to her great emotionality, but the responsibility for the conflict with John they blamed mainly on the bishop’s enemies, who set the ruler against him.